Identification of major causes and strategies adapted by chauffeurs to coombat miro-sleepiness - Navaratne, S.B.; Wickramasinghe, I. (My University, 2017)
attached

Micro-Sleepiness (MS) is a type of temporary biological phenomenon, which can happens from fraction of second to 30 seconds and fails to respond for some arbitrary sensory inputs. It has become one of the major social concerns that cause fatalities, material losses, productivity and quality reductions and eventually negative impact on national GDP. Two surveys were conducted by interviewing relevant person and investigating documentary evidence available in Sri Lanka Police Traffic Statistics Division to identify major causes and current practices adapted to combat it. The collected data were analyzed using Pareto technique. The study reveals 80% of MS is caused by Food habits, Psychological state, Diurnal factors and Bodily status of the affected party. Further 80% practices to suppress MS were Boosting the self-confident level, keep on mortar function, using chemical energy, creating gustatory stung, astonish olfactory and tingling actions. According to the survey MS occur from 14.00 to 16.00h (peak time), 16.00 to 18.00h (least) and again reappearing to some extent from 18.00 to 20.00h.This finding is being in compliance with the Sri Lanka Police Traffic statistics, because road accidents are also befall on the same time intervals.